Effect of Nd:YAG laser in the bond strength of fiberglass posts - Zanatta, Rayssa Ferreira; Fonseca, Beatriz Maria da; Steves, Stella Renata; Torres, Carlos Rocha Gomes; Gonçalves, Sergio Eduardo Paiva (Brazilian Dental Science, 2015)
The aim of the present study was to compare the effects of Nd:YAG laser application in root canals on bond strengths of fiber posts. Thirty single-rooted bovines were randomly divided into three groups (n=10); root canal instrumentation was performed, and pretreatment was conducted as follows: C group: conventional treatment (without laser irradiation); ALC group: Nd:YAG laser was applied after adhesive; and LAC group: Nd:YAG laser was applied before adhesive. The fiber posts Rebilda 15 DC (Voco) were cemented with an adhesive system and resin cement, in accordance with the manufacturer’s instructions. Six slices with 1.0mm height was obtained for of each root and bond strength was measured by push-out test using a universal testing machine (0.5 mm/min). Data were analyzed using Kruskal-Wallis and Dunn’s tests (p